Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.17761/2021-d-20-00008
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for Substance Use Disorder in Women: A Systematic Review

Abstract: It has been suggested that yoga may be an effective adjunct intervention in the management of substance use disorders (SUD). Additionally, women with SUD require different treatment approaches than men. The objective of this study was to critically evaluate the evidence for the effectiveness of yoga, specifically for women, as part of treatment for SUD. Nine electronic databases were searched from inception to January 2020. Randomized controlled trials (RCT) that evaluated any type of yoga, including yoga as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(175 reference statements)
0
7
0
1
Order By: Relevance
“…Mothers who are unable to overcome the limitations strictly risk impaired labor progress [34,35]. Performing such regular physical activities as prenatal gentle yoga, swimming, and walking, increases the ability of the body and mind to struggle with pain during birth [36]. Mothers with high confidence in regulating physical activity are less likely to experience anxiety, either during labor or postpartum period [37].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who are unable to overcome the limitations strictly risk impaired labor progress [34,35]. Performing such regular physical activities as prenatal gentle yoga, swimming, and walking, increases the ability of the body and mind to struggle with pain during birth [36]. Mothers with high confidence in regulating physical activity are less likely to experience anxiety, either during labor or postpartum period [37].…”
Section: Discussionmentioning
confidence: 99%
“…Interest in mindfulness-based interventions for the treatment of adult psychological disorders has increased significantly over the past two decades (Goldberg et al, 2018). Mindfulness and yoga interventions have been shown to be effective with both clinical and non-clinical concerns including depressive symptoms, anxiety, dysphoria, burnout, rumination, pain conditions, smoking and addictive disorders, and overall quality of life (Brooks et al, 2021;Goldberg et al, 2018;Grensman et al, 2018;Hunt et al, 2018;Liu et al, 2022;Schuver & Lewis, 2016). We summarized the results of select research studies with adult populations below.…”
Section: Research With Adult Populationsmentioning
confidence: 99%
“…Similarly, Brooks et al (2021) conducted a meta-analysis to determine the effectiveness of adjunct interventions, such as yoga, in the management of substance use disorders in women. Of the 10 randomized controlled trials included in the analysis, eight suggested that various forms of yoga have minimal to moderate significance for the treatment of addictions to alcohol, opioids, tobacco/nicotine, and mixed substances.…”
Section: Research With Adult Populationsmentioning
confidence: 99%

Mindfulness and Yoga

Arrastia-Chisholm,
Adams,
Cakmakci
et al. 2024
Int. J. PWB
“…A 2021 systematic review explored the outcomes of yoga for substance use disorder exclusively in women. The majority of included literature supported the use of various types of yoga, primarily Hatha yoga, with favourable outcomes observed for substance use prevention [19].…”
Section: Exercise Interventionsmentioning
confidence: 99%